Adherence to Mediterranean Diet of Breastfeeding Mothers and Fatty Acids Composition of Their Human Milk: Results From the Italian MEDIDIET Study - Di Maso, Matteo; Bravi, Francesca; Ferraroni, Monica; Agostoni, Carlo; Eussen, Simone R. B. M.; Decsi, Tamás; Quitadamo, Pasqua A.; Tonetto, Paola; Peila, Chiara; Profeti, Claudio; Salvatori, Guglielmo; Kazmierska, Iwona; et al. (Frontiers in Nutrition, 2022)
Background and aims: Fatty acids (FA) content in human milk may be influenced by maternal nutrition. We evaluated the role of Mediterranean diet in influencing FA milk content among 282 breastfeeding mothers participating in the MEDIDIET study. Material and Methods: Mediterranean Diet Score (MDS), a composite index, was used to evaluate the adherence to the Mediterranean diet. It includes 9 components (i.e., vegetables, fruit, cereals, legumes, monounsaturated to saturated FA ratio – MUFA/SFA, fish, dairy products, meat, and alcohol) and therefore ranges from 0 (no adherence) to 9 (complete adherence) points. None of the mothers obtained the highest score due to the low alcohol consumption in study population. Mothers were categorized in approximate tertiles of adherence: 0-3 (34.40%), 4 (26.24%), and 5-8 points (39.36%). The mean FA content across categories of MDS were compared using ANOVA and the test for trend. Results: A high adherence to the Mediterranean diet was associated with lower milk content of SFA (42.58±4.36 for MDS=0-3, 42.58±4.89 for MDS=4, and 40.92±5.22 % of fats for MDS=5-8 points; p ANOVA and p for trend=0.02). Conversely, a high adherence was associated with higher milk content of MUFA (43.27±4.27 for MDS=0-3, 43.27±4.47 for MDS=4, and 45.24±5.22 % of fats for MDS=5-8 points; p ANOVA and p for trend<0.01), ω-3 FA (1.07±0.25 for MDS=0-3, 1.22±0.49 for MDS=4, and 1.31±0.51 % of fats for MDS=5-8 points; p ANOVA and p for trend<0.01), and the major types of ω-3 FA (i.e., α-linolenic acid – ALA, eicosapentaenoic acid – EPA, decosahexaenoic acid – DHA, docosapentaenoic acid – DPA). These associations were mainly driven by the adherence to the vegetables, MUFA/SFA, fish, and dairy products components of the Mediterranean diet. Conclusions: A high adherence to the Mediterranean diet was associated with lower milk content of SFA and higher content of MUFA and ω-3 FA, including DHA. The Mediterranean diet may contribute in a milk production with higher content of specific FA which are directly involved in infant’s neural and visual development, as reported by previous studies.